Synthesis of New Pt(II) Complex Bearing Organoselenium Ligands and Evaluation of Cytotoxic Activity of Some Structurally Related Pd(II) Complexes - Ninko Radenković; Marina Kostić; Nataša Đorđević; Zana Doličanin; Tanja Soldatović; Marko Živanović; Vera M Divac (Macedonian Journal of Chemistry and Chemical Engineering, 2020)
Herein we report the synthesis of new trans-bis(2-phenylselenylmethyl)oxolane)dichloroplatinum(II) complex Pt1. Newly synthetized complex, together with two, structurally related trans-Pd(II) complexes (trans-bis(2-(phenylselenylmethyl)oxolane)dichloropalladium(II) Pd1 and trans-bis(2-(phenylselenylmethyl)oxane)dichloropalladium(II)) Pd2, were screened for cytotoxic activity through in vitro study on the HCT-116 colorectal carcinoma cell line and on the MRC-5 healthy lung pleura cell line. Activity of complexes was assessed by comparing it to the cisplatin. The cells viability and proliferation were determined using MTT assay.